Welfare State dalam Urgensi Land Banking di Indonesia - Desy Nurkristia Tejawati; Fries Melia Salviana; Shanti Wulandari (Universitas Muhammadiyah Purwokerto, 2021)
The high demand for housing has caused land prices to soar. This of course makes it difficult to build affordable housing for Low-Income Communities in urban areas. As a result, they will try to find a place to live as much as they can, such as by the river or railroad. Of course this is another problem in urban areas. Problems that can arise are flooding, environmental pollution, and the emergence of slum settlements. The alternative in solving this problem is the availability of land at an affordable price or with the Land Banking Principles to achieve community welfare. Based on the above background, the formulation of the problem can be described, namely how the Legal Characteristics of Land Banking and the application of Land Banking in Indonesia based on the Welfare State perspective. While the purpose of this research is of course to find and analyze the legal characteristics of Land Banking and to analyze and find the application of Land Banking in Indonesia from the perspective of Welfare State. This research is a normative juridical research or literature law research by examining existing literature, both primary and secondary legal materials, using a statutory and conceptual approach to later categorization and analysis.Land bank is a land policy where there is state authority either from the government itself or from an independent institution that has the authority to acquire, manage, regulate and distribute abandoned land for public purposes according to government programs. The concept of Land Banking, which is a land policy where there is state authority either from the government itself or from an independent institution that has the authority to acquire, manage, regulate and distribute abandoned land for public purposes according to government programs. This concept can be said to be a concept as an attempt by the government to fulfill its obligations in order to achieve the welfare of society by making a policy. The government made a Land Banking policy because land is an important element for the community as a place to live. Meanwhile, the residence itself can be said to be the primary need of the community. So that if the primary needs are achieved, the welfare of the community will also be achieved. Of course, in this case the organizer of the Land Banking concept is expected to be the government itself, so that later this concept will not be shifted from the original goal, namely for the welfare of the community. In addition, it is hoped that the policy can be made in written form so as to guarantee legal certainty.Keywords: Welfare State, Land Banking, Society